The Perceived Ease of Use of Mobile Payment Systems toward Consumer’s Purchasing Interest - Agus Dharmanto; Andrian (East Asian Journal of Multidisciplinary Research, 2022)
The aim from this research is to know how far the mobile payment system which applied in many conditions and by many people nowadays can affect the consumer’s purchasing interest. The purpose of this research is to inform that most of the people right now tend to change their lifestyle into millenium lifestyle which used many mobile payment systems in order to deal with everything they want in their living activities. The research methodology used is descriptive quantitative research and simple linear regression analysis. The data obtained from those management students especially the class of 2018 and 2019 which includes several tests, Validity Test, Reliability Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Simple Linear Regression Test, Hypothesis Test (partially t test and simultanous F test) and Determination Coefficient Test (adjusted r2).